2019
DOI: 10.1115/1.4042010
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Fuel Property Effects on Lean Blowout in an Aircraft Relevant Combustor

Abstract: This paper describes results from an experimental study on influences of liquid fuel properties on lean blowout (LBO) limits in an aero-type combustor. In particular, this work aimed to elucidate the roles of fuel chemical and physical properties on LBO. Fuel chemical properties stem from the fuel chemical structure, thus governing chemical kinetic behaviors of oxidation characteristics (e.g., ignition or extinction time scales) and others (e.g., fuel thermal stability or sooting tendencies). Fuel physical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…For example, lower atomization quality injectors will inherently emphasize vaporization/atomization characteristics of the flame, while better atomizing systems may push the system closer towards premixed, kinetically limited characteristics. Similarly, the Rock et al [25] data show how the controlling processes change with air temperature, presumably for similar reasons related to how quickly the fuel vaporizes .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, lower atomization quality injectors will inherently emphasize vaporization/atomization characteristics of the flame, while better atomizing systems may push the system closer towards premixed, kinetically limited characteristics. Similarly, the Rock et al [25] data show how the controlling processes change with air temperature, presumably for similar reasons related to how quickly the fuel vaporizes .…”
Section: Introductionmentioning
confidence: 75%
“…A summary of the findings from this study is shown in Figure 1, where the blowout boundaries are plotted against the DCN at 450 K (left) and the 90% boiling point temperature, T90, at 300 K (right). The DCN correlated best with the blowoff fuel-air ratios at 450 K and 550 K. The few fuels that didn't follow the DCN correlation (e.g., S2) have strong preferential vaporization characteristics; incorporating these effects into these correlations substantially improves the correlation [19,25]. Consistent with the findings of Burger et al [12], blowoff correlated best with fuel vaporization processes at 300 K. At this lower air temperature, the low T90 fuels were the most blowoff resistant and the high T90 fuels blew out the easiest.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Here, prevaporized liquid fuels have the potential to separate physical and chemical processes, allowing studying the combustion properties of different fuels based on their chemical properties alone. One important aspect is the lean blow-out (LBO) limit of different fuels [7][8][9] and hence also the dynamics of the lean blow-out process [10][11][12]. Since this process is highly dynamic and occurs on timescales on the order of milliseconds, optical diagnostics with high spatio-temporal resolution are necessary in order to fully resolve this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…This specification ensures the safe usage, fungibility, performance, and compatibility of the SAF under standard usage and severe operability conditions. Specifically, Tier 3 engine operability tests focus on fuel effects under the so-called figure-of-merit (FOM) limit phenomena, namely, lean blowout (LBO), high-altitude relight, and cold-start ignition [6][7][8]. Because of the broad range of potential physical and chemical properties of a new SAF, extensive combustor testing is needed to overcome uncertainty and ensure safety for FOM operability issues.…”
Section: Introductionmentioning
confidence: 99%